ANTIDYSLIPIDEMIA AND ANTIOXIDANT ACTIVITY OF ANDROGRAPHOLIDE COMPOUND FROM SAMBILOTO (ANDROGRAPHIS PANICULATA) HERB - Warditiani, Ni Kadek; Susanti, Ni Made Pitri; Arisanti, Cokorda Istri Sri; Putri, Ni Putu Rika Dharma; Wirasuta, I Made Agus Gelgel (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The aim of this study was to observe the antidyslipidemic and antioxidant activity of andrographolide (AND) compound from Sambiloto (Andrographis paniculata) herb. The antidyslipidemic activity could be described by lowering TC (total cholesterol), TG (triglyceride), and LDL (low-density lipoprotein) level in the blood and by increasing HDL (high-density lipoprotein) level in the blood. The antioxidant activity could be described by inhibiting the ox-LDL (oxidized low-density lipoprotein) formation. Methods: AND was separated from the sambiloto ethanolic extract. Atherosclerosis in rats was induced by rich fat food (5% yolk, 10% lard), 1% calcium and 20.000 IU vitamin D3 for 90 d. The rats were treated with AND compound on the 61st day for 30 d. On the 90th day, the blood of rats had been collected, and its blood vessel was also extracted. Antidyslipidemic activity was measured by estimating the level of TC, TG, LDL and HDL in the blood. Antioxidant activity was measured by calculating the ox-LDL concentration in blood and histopathology parameter. Results: 18 mg/kg BW AND could reduce the level TC, TG, and LDL in blood, and could increase HDL blood level significantly (p<0.05). This compound can also significantly inhibit LDL oxidation (p<0.05), and the histopathology result showed that this compound could protect the vessel from adhesive lipid plaques. Conclusion: AND compound from sambiloto herb showed the antidyslipidemic and antioxidant effect in atherogenic rats.